John Philip Duck - Polacco, Patricia (New York : Philomel Books, 2004)
During the Depression, a young Memphis boy trains his pet duck to do tricks in the fountain of a grand hotel and ends up becoming the Duck Master of the Peabody Hotel.
2.9
K-3
Keywords: Ducks -- Fiction; Hotels, motels, etc. -- Fiction; Memphis (Tenn.) -- Fiction; Historical fiction; Ducks -- Fiction; Hotels and motels -- Fiction; Memphis (Tenn.) -- Fiction; Historical fiction